MINIMALISM VS. CONSUMERISM: An Islamic Perspective on Indonesian Gen Z Social Media Influence - Kurlillah, Anis; Nurfadillah, Nurfadillah; Fazal Ahmed, Osman Abulkalam; AL Bakri, Mirdat; Munadiati, Munadiati (IAIN BONE, 2025)
AbstractThis study investigates the potential of minimalist lifestyle trends, emerging as a counter-narrative on these platforms, to influence the consumerist behavior of this demographic from an Islamic economic perspective. Rapid technological advancements have significantly impacted lifestyles, notably fostering consumerism among Indonesian Generation Z, often fueled by social media platforms like TikTok. Employing a qualitative descriptive analytical approach, this research examines the extent to which the application of minimalist principles can impact consumerism among Indonesian Gen Z. The findings indicate that while a minimalist lifestyle holds considerable potential to curb consumerism, its full implementation is hindered by deeply ingrained consumerist habits driven by social media trends. This study concludes that understanding and applying minimalist principles, informed by Islamic economic teachings emphasizing moderation and the avoidance of extravagance, can offer a viable alternative to the prevailing consumer culture among Indonesian Generation Z. The implications of this research lie in providing insights for educators, policymakers, and Islamic institutions seeking to promote balanced consumption patterns among youth in IndonesiaÂ